Knowledge regarding prevention of post traumatic compartment syndrome of limbs among nurses of a teaching hospital - Pokharel, Kalpana (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Acute compartment syndrome is a serious complication of limb trauma. This is associated with significant morbidity if not diagnosed and treated urgently and effectively on time. Nurses’ Knowledge regarding compartment syndrome is one of the important measures for early diagnosis and prevention. This study aims to assess the knowledge regarding the prevention of post-traumatic compartment syndrome of limbs among nurses of a Teaching Hospital.Method:  Descriptive cross-sectional study was conducted to assess the knowledge regarding the prevention of post-traumatic compartment syndrome of limbs at Patan Hospital, Nepal from 12 August to 7 September 2018. Total enumerative sampling technique was used among nurses from surgical, orthopedic, private, and emergency. Data was collected using a structured self-administered questionnaire and analyzed using SPSS version 16.Result: Out of 90 nurses, 38(42.22%) had an adequate level of knowledge, 29(32.22%) had a moderate level of knowledge and 23(25.56%) had an inadequate level of knowledge regarding the prevention of post-traumatic compartment syndrome of limbs. There was no significant association between age, level of education, working experience, working area, and level of knowledge. Working experience in the orthopedic ward had a significant association with the level of knowledge.Conclusion:  Nearly half of the respondents had an adequate level of knowledge regarding the prevention of post-traumatic compartment syndrome of limbs. Nurses working in the orthopedic ward had a good level of knowledge than working in other words.